2020
DOI: 10.3390/f11090981
|View full text |Cite
|
Sign up to set email alerts
|

Organic Carbon Stabilization Mechanisms in Mangrove Soils: A Review

Abstract: Despite the recognized organic carbon (OC) sequestration potential of mangrove forests, the ongoing climate change and anthropogenic disturbances pose a great threat to these ecosystems. However, we currently lack the ability to mechanically understand and predict the consequences of such impacts, primarily because mechanisms underlying OC stabilization in these ecosystems remain elusive. Research into OC stabilization has focused on terrestrial soils and marine sediments for decades, overlooking the vegetated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 96 publications
(207 reference statements)
0
43
0
Order By: Relevance
“…This observation is quite close to a previous study that states 77% of total carbon stock in the mangrove ecosystem was stored in soil (Alongi 2020;Kauffman et al 2014;Sasmito et al 2020b). Coastal ecosystem are known to have higher carbon accumulation in sediments/soil compared to terrestrial vegetation mainly because of high autochthonous and allochthonous inputs and low decomposition rates of organic matter due to the mostly anoxic conditions in the sediment (Kristensen 2000;Donato et al 2011;Kida and Fujitake 2020). The rate of organic carbon accumulation in mangrove ecosystems is estimated to be around 20 -24 Tg C yr −1 (Twilley et al 1992;Jennerjahn et al 2004).…”
Section: Soil Properties and Soil Carbon Stockmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is quite close to a previous study that states 77% of total carbon stock in the mangrove ecosystem was stored in soil (Alongi 2020;Kauffman et al 2014;Sasmito et al 2020b). Coastal ecosystem are known to have higher carbon accumulation in sediments/soil compared to terrestrial vegetation mainly because of high autochthonous and allochthonous inputs and low decomposition rates of organic matter due to the mostly anoxic conditions in the sediment (Kristensen 2000;Donato et al 2011;Kida and Fujitake 2020). The rate of organic carbon accumulation in mangrove ecosystems is estimated to be around 20 -24 Tg C yr −1 (Twilley et al 1992;Jennerjahn et al 2004).…”
Section: Soil Properties and Soil Carbon Stockmentioning
confidence: 99%
“…Nevertheless, studies regarding the factors that influence carbon storage in the mangrove ecosystem are scarce, including which species and geography significantly impact carbon storage (McLeod et al 2011;Howard et al 2017). Few studies have observed the factors that influence carbon preservation in mangrove ecosystem (Matsui et al 2015;Weiss et al 2016;Martuti et al 2017;Asadi et al 2018;Pérez et al 2018;Gao et al 2019;Kida and Fujitake 2020). Findings of these studies showed that the influencing factors of carbon sequestration in the mangrove ecosystem were varied and complicated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the factors controlling this depth distribution are poorly understood (Castañeda-Moya et al, 2011;Muhammad-Nor et al, 2019), and it is currently unknown how reforestation might affect the depth distribution of mangrove root production. This knowledge is important for estimating the quantity and quality of carbon stored in reforested mangroves, as a major source of slow-cycling organic carbon in soils is thought to derive from fine roots (Rasse et al, 2005;Kida & Fujitake, 2020). McKee et al (2007) and Xiong et al (2017) both showed that the accumulation of fine roots (which they defined as having diameter < 2.5 mm and < 1 mm, respectively) was a major contributor of SOM accumulation in mangroves, and correlated significantly with soil surface elevation in mangroves.…”
Section: Background and Rationalementioning
confidence: 99%
“…On the contrary, the fungal community was evenly distributed according to the above criteria and showed a dominance of Ascomycota over Basidiomycota in all analyzed layers [ 3 ]. Mangroves are considered to be the largest carbon reservoir in coastal ecosystems and actively supply carbon to adjacent ecosystems [ 5 , 6 ]. In this carbon-rich environment, mangrove fungi play a key role in the recycling of organic matter, including Lignocellulose-rich biomass [ 7 ].…”
Section: Introductionmentioning
confidence: 99%